Food markets and nutrition in the Democratic Republic of the Congo (2004–2005) - Marivoet, Wim (International Food Policy Research Institute, 2016)
Inspired by the ongoing process of decentralization and in an effort to inform local and national policy makers concerned with food security, this paper provides a descriptive but detailed geographical overview of Congo’s food markets as well as the nutritional status of its population. To do so, this paper will mainly rely on the 1-2-3 budget survey data, conducted in 2004–2005. Along both dimensions, access to food and nutrition, a good deal of spatial variation exists. First, overall efficiency of domestic food markets seems extremely poor. The capital city of Kinshasa is a good example of this; it is food deficient and poorly connected to its own hinterland and therefore highly dependent on foreign food imports. Markets in the former provinces of Kasaï, in the center of the country, and the conflict-prone northeastern part of the country are two minor exceptions, as food prices are slightly more equal. Furthermore, the most competitive food producers are found in Équateur and North Kivu. Notwithstanding these differences in food access, about five diet types can be identified. The most energy-rich diet is based on cassava and palm oil, typically consumed in Maniema, Orientale, Équateur, and rural Bas-Congo. As a result, these provinces on average display higher calorie intakes. Apart from diet composition, income levels and prevailing nonfood needs also determine energy sufficiency. For these reasons households in Katanga and North Kivu are relatively well nourished too, while urban dwellers in Bas-Congo and Orientale (contrary to their corresponding rural sector), and especially households in South Kivu and Kinshasa, suffer from large calorie deficiencies.